Does the Porn Star Blush? Performing the Real in Post-transgressive Cinema - Blake, Charlie; Johnson, Beth (Academic Quarter | Akademisk kvarter, 2011)
A more philosophically-oriented discussion of transgression and the heteronormative comes in Charlie Blake and Beth Johnson’s article Does the Porn Star Blush?, where they discuss ideas of post-transgression in the representation of explicit sexual acts in film, where non-pornographic modes of representation may point towards a search for authenticity in the cinematic image.